Exporting electrons. Issue 11 (November 2018) - Toit, Andrea
This study identifies a novel and simple electron transport chain inListeria monocytogenes, whereby electrons are transported from intracellular NADH to quinone and subsequently via an extracellular flavoprotein to a terminal electron acceptor.